Indonesian Language Learning Assistance for Foreign Speakers (BIPA) at the Indonesian Embassy in Ankara, Turkey - Aria Septi Anggaira (International Journal of Community Engagement Payungi, 2023)
Indonesian until now has been taught to foreigners in various institutions both at home and abroad. This learning program is known as the Indonesian for Foreign Speakers (BIPA).  This study aims to give an assistance of Indonesian language learning for foreign speakers of turkey. During the Covid-19 pandemic, BIPA learning was carried out online. Turkey is one of the countries whose citizens have a considerable interest in studying Indonesian. The researchers used Service Learning (SL) approach (Felten, & Clayton, 2011). It as a medium for integrating voluntary community service with active reflection which is expected to enrich and strengthen the material about bringing oral storytelling in developing students and teachers. The method of this study is by giving an assistance of Indonesian language learning. The BIPA program at the Indonesian Embassy in Ankara Turkey has been going on for 2 periods. In the 2nd period, which was implemented from October 9 to December 15, 11 classes and 4 BIPA levels have been carried out well. This is evidenced by the results of the final examination of the program obtained by the learners, namely by increasing the Indonesian language competence of  the learners. The results obtained by   the learners at the  end of the program showed that their Indonesian language  competence was improved. Thus, in the future this program is expected to continue so that more learners can take part in the BIPA  program  implemented at the  Indonesian Embassy in  Ankara, Turkey either  online or in-person learning. Thus, the BIPA learning program can continue to be implemented in the future.